2020
DOI: 10.3390/nu12030669
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pomace Matrix and Cyclodextrin Encapsulation on Olive Pomace Polyphenols’ Bioaccessibility and Intestinal Permeability

Abstract: Olive pomace is a rich source of biologically active compounds, mainly polyphenols. Recently, an efficient and sustainable cyclodextrin (CD)-enhanced extraction was developed. It enabled a relatively simple formulation of high-quality olive pomace extracts (OPEs) that can be used as alternative sources of olive-derived polyphenols in the nutrition and pharma industries. However, biological effects and nutraceutical potential of OPEs are primarily limited by generally low oral bioavailability of major polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
5
17
0
Order By: Relevance
“…The results showed that rutin had an encapsulation efficiency of 83.7 % (which was the highest) using 1,1′-carbonyldiimidazole as cross-linker in a 1:3 ratio of nanosponge/cross-linker, while phloridzin (87.2%) and chlorogenic acid (77.5 %), with best results seen with HMDI. Radic et al. (2020) evaluated the influence of olive pomace extracts matrix and cyclodextrins (CDs) on bio-accessibility and intestinal permeability of main olive pomace polyphenols.…”
Section: Innovative Technology For Mycotoxin Detoxificationmentioning
confidence: 99%
“…The results showed that rutin had an encapsulation efficiency of 83.7 % (which was the highest) using 1,1′-carbonyldiimidazole as cross-linker in a 1:3 ratio of nanosponge/cross-linker, while phloridzin (87.2%) and chlorogenic acid (77.5 %), with best results seen with HMDI. Radic et al. (2020) evaluated the influence of olive pomace extracts matrix and cyclodextrins (CDs) on bio-accessibility and intestinal permeability of main olive pomace polyphenols.…”
Section: Innovative Technology For Mycotoxin Detoxificationmentioning
confidence: 99%
“…Olive pomace and olive pomace wastewater, the residues left after the production of olive oil, are secondary raw materials that contain significantly higher amounts of olive polyphenols compared to olive oil, particularly hydroxytyrosol (HTS) and tyrosol (TS). Numerous green extraction methods for efficient extraction of polyphenols from olive mill waste were recently developed [ 3 , 4 , 5 , 6 ], and significant steps forward have been taken in developing functional formulations of olive pomace extracts (OPEs) that will ensure satisfactory composition, stability, bioavailability, and biological activity of major active compounds, primarily HTS and TS [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…OPEs are generally richer sources of HTS and TS in comparison to extra-virgin olive oil, but they have rarely been investigated in terms of bioavailability. Recent data obtained by Radić and co-authors [ 8 ] show that OPE polyphenols are stable during gastrointestinal digestion (88–187%; due to degradation of secoiridoids and formation of HTS and TS during digestion). Investigation of permeability showed that HTS and TS are primarily absorbed by passive diffusion and that absorbed oleuropein is extensively metabolized in Caco-2 cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations